Alternative Dispute Resolution - When It Works, When It Doesn't - Messick, Richard E. (World Bank, Washington, DC, 2012)
Alternative dispute resolution encompasses arbitration, mediation, conciliation, and other methods-short of formal litigation-for resolving disputes. Alternative dispute resolution offers several advantages over a lawsuit. It is less adversarial and in some cases can be faster and less expensive. It can also reduce court workloads. For these reasons its use is being promoted by court reformers in many developing and transition economies.